Adição de gás ozônio ao diluente de sêmen equino submetido a congelação: efeito sobre a viabilidade das células espermáticas - Macêdo, Iara Nóbrega (2021)
The objective of this study was to evaluate the effects of the addition of different concentrations of ozone to the semen of quarter horse submitted to cryopreservation. Six ejaculates from four stallions (n=24) were collected. The ejaculates were divided and added to four experimental groups: control group composed only of the freezing extender (BotuCRIO®) and three other groups with freezing extender (BotuCRIO®) ozonized at concentrations of 6, 8 and 12 μg of O3/mL. The semen samples were diluted (200 x 106 spermatozoa/mL), filled in reeds and frozen. After defrosting (37 ºC, 30s), the samples were evaluated at moments 0, 30 and 60 minutes of incubated regarding spermatic kinetics, plasma membrane integrity (PMI), acrossome integrity (ACi) and mitochondrial membrane potential (MMP). Kinetic parameters were evaluated using the computerized system of spermatic analysis (CASA), and cellular integrity tests were performed under epifluorescence microscopy through the use of fluorescent probes. There was is reduction in kinetic parameters (TM, PM, VCL, VSL and VAP) in all groups during the thermoresistance test (TT), a pattern also found in PMI and MMP analyses (p<0.05). For the kinetic parameters of TM, LIN, STR, WOB, ALH and BCF there was no difference (p>0.05) between the control group and the treatments (6, 8 and 12 μg of O3/mL), in any of the evaluated times. Regarding the Parameters VCL, VSL and VAP, the group treated with 6 μg did not differ from the control or from 8 μg, but was higher than 12 μg at 30 and 60 minutes. ACi and PMI showed no difference between groups (p>0.05) and PMI was lower in groups 8 μg and 12 μg compared to control and 6 μg (p<0.05). It is concluded that the addition of ozone does not present beneficial effects for cryopreservation of equine semen at the concentrations used and decreases important parameters for fertility.